Importance Index of Mangrove Ecosystems in Kampung Baru Village, Penajam District, North Penajam Paser Regency - Muhammad Yasser; Hendri Hendri; Omega Raya Simarangkir; Aditya Irawan; Lily Inderia Sari (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Mangroves are plants that grow between tidal lines. Mangrove forests have very important ecological andeconomic functions, but are very vulnerable to damage if they are not wise in maintaining, conserving andmanaging them. This research was conducted in Kampung Baru Village, Penajam District, Penajam PaserUtara Regency, East Kalimantan Province. The purpose of this study was to identify the types ofmangroves and to determine the ecological conditions of mangrove forest vegetation in the mangroveecosystem of Kampung Baru Village. The method used is the Transect Line Plot method. The dataobtained were then processed by community structure analysis. The types of mangroves found in fourstations in the mangrove ecosystem of the Kampung Baru, consist of nine types of mangroves, namely:Rhizopora mucronata, Rhizopora apiculata, Ceriops decandra, Avicennia marina, Nypa, Avicennia alba,Avicennia officinalis, Avicennia rumphiana, Sonneratia alba, and from four families, namely:Rhizophoraceae, Sonneratiaceae, Canthaceace and Arecaceace. The highest density value was Rhizophoramucronata, namely 1.04 ind/m2, with a relative density of 149.8%. The highest frequency value for Rhizophora mucronata was 400. The highest value for closure was Avicennia alba (100.12 m2). Importance value index of Rhizophora mucronata (151.82%), the lowest analysis of all stations wereCeriops decandra and Nypa species and had very abundant species diversity.